A concise formal total synthesis of lactimidomycin1. Issue 41 (21st May 2015) - Li, Wei; Georg, Gunda I.
<x xml:space="preserve">Abstract</x> An ene–yne coupling/alkyne reduction tandem ring-closing reaction was employed for the formal total synthesis of the anti-tumor natural product lactimidomycin.